The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3847/1538-4357/aabb56
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiar Radial Distribution of Multiple Populations in the Massive Globular Cluster M80

Abstract: We present a detailed analysis of the radial distribution of light-element multiple populations (LE-MPs) in the massive and dense globular cluster M 80 based on the combination of UV and optical Hubble Space Telescope data. Surprisingly, we find that first generation stars (FG) are significantly more centrally concentrated than extreme second generation ones (SG) out to ∼ 2.5r h from the cluster center. To understand the origin of such a peculiar behavior, we used a set of N-body simulations following the long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 60 publications
(75 reference statements)
3
66
0
Order By: Relevance
“…Therefore, these findings make ω Cen one of the few stellar systems currently known where metal-rich stars have a more extended spatial distribution compared to metal-poor stars. A similar behavior has been observed in the cluster M 80, where Dalessandro et al (2018) found that the stellar subpopulation enriched in Sodium (Na) and depleted in Oxygen (O), which they identify as the second generation, has a more extended spatial distribution compared to the cluster main stellar sub-population (the first generation), which is Na-poor and O-rich. The authors claimed that the two stellar sub-populations have a different helium content and this causes a mass difference, resulting in spatial segregation of the stars, with the lower mass second-generation stars having a more extended spatial distribution.…”
Section: Introductionsupporting
confidence: 76%
“…Therefore, these findings make ω Cen one of the few stellar systems currently known where metal-rich stars have a more extended spatial distribution compared to metal-poor stars. A similar behavior has been observed in the cluster M 80, where Dalessandro et al (2018) found that the stellar subpopulation enriched in Sodium (Na) and depleted in Oxygen (O), which they identify as the second generation, has a more extended spatial distribution compared to the cluster main stellar sub-population (the first generation), which is Na-poor and O-rich. The authors claimed that the two stellar sub-populations have a different helium content and this causes a mass difference, resulting in spatial segregation of the stars, with the lower mass second-generation stars having a more extended spatial distribution.…”
Section: Introductionsupporting
confidence: 76%
“…In light of the results of Dalessandro et al (2018b), who used artificial star tests to infer that their star counts are complete at a > 95% level, no incompleteness corrections were applied. The resulting surface density profiles for the four populations are shown in Fig 2. As the photometry of Dalessandro et al (2018a) is limited to the central region of the cluster, we complemented our global number density profile with the Gaia data recently presented by de Boer et al (2019). After accounting for a vertical offset, the two profiles were stitched together.…”
Section: Radial Density Profilesmentioning
confidence: 99%
“…In this paper, we study the globular cluster NGC 6093 (M80). Dalessandro et al (2018a) recently found the three detected populations to be unusually distributed, with the primordial population being more centrally concentrated than the intermediate (in terms of N-enrichment) population, which in turn is more centrally concentrated than the extreme population. NGC 6093 is considered to be dynamically old (Ferraro et al 2012), in which case the different concentrations are unlikely to be a relic from the formation of the cluster.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations